2021
DOI: 10.1525/elementa.2020.00104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in summertime surface ozone in the Southern Front Range of the U.S. Rocky Mountains

Abstract: Summertime ozone in the Western United States presents a unique public health challenge. Changes in population, background ozone, wildland fire, and local precursor emissions combined with terrain-induced meteorology can affect surface ozone levels and compliance with the National Ambient Air Quality Standards (NAAQS). While there is considerable research on ozone in the Northern Front Range Metropolitan Area of Colorado, United States, less is known about the Southern Front Range. In Colorado Springs, approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These were used to track trends and relationships with other variables from 2010 to 2019. Data for the year 2020 was not used because of frequent wildfire smoke (Albores et al., 2023; Flynn et al., 2021). Data were acquired for the FTCW, WCT, RFLAT, NREL, and CHAT sites.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…These were used to track trends and relationships with other variables from 2010 to 2019. Data for the year 2020 was not used because of frequent wildfire smoke (Albores et al., 2023; Flynn et al., 2021). Data were acquired for the FTCW, WCT, RFLAT, NREL, and CHAT sites.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…Similarly, Abeleira and Farmer (2017) found that ozone in the Denver urban area was either stagnant or increasing between 2000 and 2015, despite substantial reductions in NOX emissions. In Colorado Springs, approximately 100 km south of Denver, Flynn et al (2021) found that summertime MDA8 ozone shows no significant trend throughout its distribution over the past 20 years. Further, they found little evidence of local photochemical production or ozone transport from Denver, consistent with our classification of this area as rural.…”
Section: Pronounced Shift In Spatial Distribution Of Maximum Us Ozone...mentioning
confidence: 96%
“…These were used to track trends and relationships with other variables from 2010-2019. Data for the year 2020 was not used because of frequent wildfire smoke (Albores et al, 2023;Flynn et al, 2021) To test for the effects of meteorology on trends in O3, June-August mean 500 hPa heights were acquired from the National Center for Environmental Prediction (NCEP) Reanalysis for a 2.5° by 2.5° grid cell centered on 40°N 105°W which contains the DM/NFR. The NCEP Reanalysis meteorological data product is described by Kalnay et al (1996).…”
Section: Data Sourcesmentioning
confidence: 99%